Manufacturing service network characteristics analysis of digital twin system under edge computing and cloud edge collaborative computing environment. (14th June 2023) - Xiang, Feng; Zhou, Ping
In order to optimise the configuration of manufacturing services in the virtual and real space and improve the efficiency of the collaboration of manufacturing service resources, we investigate the digital twin systems that provide various services under different service computing modes, analyse their basic network structure from the perspective of complex networks, and reveal internal interaction methods and feedback control process to optimise virtual and real resource allocation and improve physical system stability. On this basis, the characteristics of the manufacturing service network in the digital twin system are further analysed and explained, and the mechanism of manufacturing service collaboration in the virtual-real interaction fusion mode is described.